ANALYSIS RELIABILITY INSTRUMENT OF LEARNING PERFORMANCE THROUGH PRINCIPAL COMPONENT ANALYSIS METHOD - SUSILAWATI (NIM: 20107051), WANGSIH
One of ways to measure reliability of teacher's learning performance is through questioner that contains some statements which relate to teacher's learning performance. From this questioner, the information about teacher's learning performance reliable or no can be obtained. Before organized data, the reliability of instrument must be test. If the reliability is good, then this instrument can be measure teacher's learning performance. Data questioner in this project are organized through principal component analysis method and spreading of principal component analysis method. Principal component analysis is analysis multivariate method with purpose to simply multivariate dimension with linear transformation way, so that new variable can be obtained, with no correlation each other, but the greater part information that exist at the beginning variable are kept. Through this method, instrument of teacher's learning performance, can be measured from points of view partial (each class), and global (union class).